Treating Relapsed Acute Lymphoblastic Leukemia in Pediatric Patients - Guitter, Myriam R. (Revista del Hospital Italiano de Buenos Aires, 2024)
An editorial commentary on the study by Makiya et al., "Treatment of Relapse in Pediatric Patients with Acute Lymphoblastic Leukemia in Argentina: Results from a Clinical Trial and a Prospective Cohort," the situation of acute leukemias in pediatrics and their relapses in Argentina and their treatment options are mentioned and contextualized.